Capital Structure, Investment Decision and Financial Performance of SMEs in Uganda (International Journal of Scientific Research and Management (IJSRM), 2022)
The paper explored the relationship between capital structure, investment decision and financial performance of SMEs in Uganda a case of Central Uganda. The study adopted a descriptive, cross-sectional and correlational design. The sample size was 226 SMEs in Central Uganda. The findings point to a moderate significant positive relationship between capital structure, investment decision and financial performance of SMEs. Capital structure and financial performance of SMEs (r = 0.642, P-value = 0.000), investment decision and financial performance of SMEs (r = 0.488, P-value = 0.000). From the results, we confirm that capital structure, investment decision, predict up to 66.2% of the change in financial performance of Small and Medium Enterprises in Central Uganda. The results show good model fits and fig.2 defines the model of capital structure and investment decisions on financial performance of SMEs in Uganda and is encompassed of 4 proportions of capital structure in terms of Equity, Long term Debt, Short term debt as well as investment decisions and their predictive power on financial performance of SMEs in Uganda. Figure 2 and table 1 and 2 clearly indicate that capital structure and investment decisions are significantly associated with return on assets (ROA) which in turn leads to improved financial performance. The study recommends an appropriate mix of capital structure coupled with premeditated investment decisions so as to have improved financial performance of SMEs in Uganda. The current study underwrites to academic research by providing empirical proof to support theories pertinent to the elucidation of financial performance. The study was anchored on Pecking Order theory together with Modigliani&Miller theory and the results depict the behaviours that managers have while making decisions concerning capital structure and investment decisions. With such, the precursors of capital structure, investment decisions on financial performance of SMEs in Uganda and other related developing countries has been revealed.